2000
DOI: 10.1002/vnl.10231
|View full text |Cite
|
Sign up to set email alerts
|

Increasing PVC suspension polymerization productivity by using temperature‐programmed reactions

Abstract: Vinyl chloride polymerizations are known to be autoaccelerating. The reaction rate increases with conversion. Because of this phenomenon, substantial reactor productivity at early conversion can be lost because the heat‐removal capacity of the reactor is not fully utilized until near the end of the polymerization. For this reason it is desirable to speed up the polymerization at the beginning and slow it down near the end. This rate adjustment can be achieved by running the polymerization hotter in the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…37 But this is always optimized with product quality in mind, including thermostability (application of different initiator results at different concentration of tertiary chlorines and chloroallyl groups). 37 But this is always optimized with product quality in mind, including thermostability (application of different initiator results at different concentration of tertiary chlorines and chloroallyl groups).…”
Section: Initiator Restsmentioning
confidence: 99%
“…37 But this is always optimized with product quality in mind, including thermostability (application of different initiator results at different concentration of tertiary chlorines and chloroallyl groups). 37 But this is always optimized with product quality in mind, including thermostability (application of different initiator results at different concentration of tertiary chlorines and chloroallyl groups).…”
Section: Initiator Restsmentioning
confidence: 99%
“…Among works performed on the enhanced productivity of PVC through temperature-trajectory [2][3][4][5][6][7][8], in earlier work [9][10][11] we suggested the most reduction in the polymerization time up to 33%. Bijanmanesh et al [13] reported that continuous dosing of a fast initiator during suspension polymerization of vinyl chloride enhanced productivity by 40%.…”
Section: Methodsmentioning
confidence: 85%
“…If the monomers are volatile at the working pressure of the reactor, then some heat can be removed relatively quickly by monomer vaporization (as discussed above for vinyl chloride polymerization; see Section 5.2.5). Longeway and Witenhafer [113] suggested that the reactor could be operated at a higher temperature in the early stages, to make full use of the cooling capacity. Pinto and Giudici [111] suggested that a mixture of initiators, with different half-lives and activation energies, could be used.…”
Section: Reaction Engineering For Suspension Polymerization 235mentioning
confidence: 99%